Earth 616, Earth 1610, Earth 3490-Wait, what universe is this again? The creation and evolution of the Avengers and Captain America/Iron Man fandom. - Coker, Catherine (Transformative Works & Cultures, 2013)
This essay surveys the creation and evolution of the Captain America/Iron Man or Steve/Tony ship in Avengers fandom, from its origin in comics to its reinterpretation by fandom through the recent movies, and discusses how the alternate universe trope in both canon and fanon is used to make a case for the pairing.